Da Ponte in New York, Mozart in New York - Biba, Otto (Current Musicology, 2006)
One might be surprised to learn that relatively few of Lorenzo da Ponte’s letters have been preserved. In one of these, written in New York in 1824 to an unknown recipient, Da Ponte names what he considered to be five of his most important and successful libretti: La cosa rara, L’ arbore di Diana, La capricciosa corretta, Le nozze di Figaro, and Don Giovanni. COSt fan tutte is not mentioned, nor does he name the composers of the stated titles-Martin y Soler and W. A. Mozart (Zagonel 1995:228ff.).